Implementasi Ayat 32 dan 33 Surat An-Nur Tentang Penyegeraan dan Penundaan Pernikahan - Nur Hidayah (Faculty of Sharia and Law UNISNU Jepara, 2020)
The discussion on the substance of verses 32 and 33 of Surah an-Nur is intended to examine more deeply the suggestion to marry or to postpone it. The consideration is that when examined textually the verse tends to appear contradictory. Therefore, it is necessary to discuss the substance of the verse, which this time will be discussed qualitatively-descriptively to capture the strategic aspects underlying the verse. The discussion is carried out by referring to the related library data. The results of the discussion show that the verse holds the meaning of strengthening monotheism to Allah SWT in determining the fate of its servants. And also Allah SWT commands us to be patient from getting married, if we are unable to provide household groceries later.Pembahasan tentang substansi ayat 32 dan 33 surat an-Nur dimaksudkan untuk mengkaji lebih mendalam tentang anjuran menikah atau menundanya. Pertimbangannya adalah bahwa ketika ayat tersebut dikaji secara tekstual cenderung tampak adanya kontradiksi. Oleh karena itu, perlu kiranya ada pembahasan substansi dari ayat tersebut, yang kali ini akan dibahas secara kualitatif-deskriptif untuk menangkap aspek-aspek strategis yang melatarbelakangi ayat tersebut. Pembahasan dilakukan dengan merujuk pada data pustaka yang terkait. Hasil dari pembahasan menunjukkan bahwa ayat tersebut menyimpan makna penguatan ketauhidan kepada Allah Swt dalam menentukan nasib hambanya. Dan juga Allah Swt Swt memerintahkan kita untuk bersabar dari menikah, jika tidak mampu memberikan belanja keperluan rumah tangga nantinya.